Positive hepatitis B surface antigen leads to a decrease in ovarian reserve in infertile patients receiving first in vitro fertilization treatment - Yutao Li; Xuejiao Wang; Ye Jiang; Qun Lv; Yi Zhang; Yu Wang (BMC Medicine)
Abstract Background This study assessed the impact of chronic hepatitis B virus (HBV) infection on ovarian reserve in women. Methods We analyzed data from 38,861 infertile women undergoing their first in vitro fertilization (IVF) treatment (2016–2022), including 1574 HBsAg-positive cases. A control group of 1574 HBsAg-negative women was matched by age and body mass index (BMI). Comparison of clinical characteristics, antral follicle count (AFC), follicle-stimulating hormone (FSH), luteinizing hormone (LH)/FSH ratio, anti-Müllerian hormone (AMH), gonadotropins (Gn) days, total Gn dosage, number of retrieved oocytes, number of mature metaphase II (MII) oocytes, and the proportion of patients with diminished ovarian reserve (DOR; AMH < 1.1 ng/ml) between two groups. Results HBsAg-positive women showed lower basal AFC and AMH, higher basal FSH, received more Gn, and had fewer retrieved and MII oocytes than HBsAg-negative women. No significant differences in ovarian reserve or stimulation outcomes were found between e antigen-positive and e antigen-negative HBV-infected groups. DOR was less prevalent in HBsAg-negative women, and logistic regression indicated a higher DOR risk with HBV infection. Conclusions HBsAg positivity significantly impairs ovarian reserve in women, but e antigen status does not notably affect it among HBV-infected individuals.